MiRNAs Regulating Insulin Sensitivity Are Dysregulated in Polycystic Ovary Syndrome (PCOS) Ovaries and Are Associated With Markers of Inflammation and Insulin Sensitivity - Cirillo, Francesca; Catellani, Cecilia; Lazzeroni, Pietro; Sartori, Chiara; Nicoli, Alessia; Amarri, Sergio; La Sala, Giovanni Battista; Street, Maria Elisabeth (Frontiers in Endocrinology, 2019)
Objective: MicroRNAs (miRNAs) are gene expression regulators. Altered miRNA levels are associated with diabetes, insulin resistance, and inflammation. Insulin resistance and inflammation are both features of Polycystic ovary syndrome (PCOS). The aim of this study was first to assess differences in selected miRNAs (miR-146a, miR-155, miR-320, miR-370, miR-486), involved in insulin sensitivity regulation and inflammation, in women with or without PCOS. Second, to investigate relationships among these miRNAs, insulin, High mobility group box 1 (HMGB1), and IL-6 in follicular fluid (FF), serum 17-beta estradiol (E2), and the number of dominant follicles. Methods: Thirty PCOS and 36 non-PCOS women undergoing in vitro fertilization were enrolled. RNA from granulosa cells (GC) and FF was extracted and the specific miRNAs were evaluated using qRT-PCR. HMGB1, insulin, and IL-6 in FF, and serum E2 were assayed using specific kits. Results: MiR-146a, miR-155, miR-486 were upregulated and miR-320 and miR-370 were downregulated in GC from the PCOS patients. In FF, miR-146a, miR-155, and miR-486 showed lower levels in PCOS, whereas miR-320 and miR-370 showed an opposite trend but no significant changes were observed. These miRNAs showed relationships with Body Mass Index, age, E2, number of dominant follicles, insulin and HMGB1. Conclusion: In conclusion, the miRNAs analyzed showed changes in PCOS ovaries and had relationships with indices of inflammation and insulin sensitivity within the ovary, providing evidence for new regulatory mechanisms.